Transfer of Ownership Rights of House Ownership Credit by Debtor to a Third Party Before Installments are Paid in Kendal Regency - Sesotya Wahyu Leksono, Syarief (TABELLIUS: Journal of Law, 2025)
This study aims to determine and analyze the process of transfer of land rights in the law of mortgage collateral (KPR), to determine and analyze the legal consequences of the transfer of land rights as collateral for mortgages (KPR) that are still in the installment period. The research approach method used in this thesis is the normative legal research method. The specifications of this study use descriptive analysis. The types of data used in this study are primary data which include the 1945 Constitution; Law Number 30 of 2004 in conjunction with Law Number 20 of 2004; Civil Code; Regulation of the Minister of Public Works and Public Housing No. 20 / PRT / M / 2019, as well as secondary data containing books and other supporting documents. Collection of research data with library materials. The data analysis method used in analyzing the data is qualitative historical analysis. The results of the study show that the transfer of ownership rights to a mortgage house from the debtor to a third party as a buyer before the installments are paid off without the creditor's approval is a legal act that is not permitted. The legal consequence of the transfer of ownership rights to a mortgage house by the debtor to a third party as a buyer before the installments are paid off without the creditor's approval is the absence of legal certainty.